Pelatihan Penulisan Cerpen Bagi Siswa Smp Negeri 1 Muaro Jambi - Fitrah, Yundi; Mestika Putra, Yoga; Putri, Aprilia Kartika; Saumia, Zulfa (Estungkara: Jurnal Pengabdian Pendidikan Sejarah, 2023)
Saat ini, budaya literasi dalam karya sastra perlu digalakkan kembali (Nur, 2020). Beberapa program pemerintah di antaranya adalah program pelatihan literasi yang dikembangkan dan dilaksanakan di sekolah. Literasi tidak hanya tentang kemampuan membaca, tetapi juga dalam bentuk keterampilan berbahasa lainnya yaitu menulis. Kementerian Pendidikan dan Kebudayaan Currently, the culture of literacy in literary works needs to be reinvigorated (Nur, 2020). Some government programs include literacy training programs developed and implemented in schools. Literacy is not only about the ability to read, but also in the form of other language skills, namely writing. The Ministry of Education and Culture Research and Technology has launched literacy programs in schools to improve students' reading skills, especially at the secondary school level. Writing skills are important to develop. In addition to the idea of writing, information conveyed through writing can also reach distant places. Furthermore, writing is now very easy to publish even through various media. Students, especially junior high school students, can write well and develop their ideas if guided properly. The Jambi University Indonesian Literature Study Program Community Service Team organized a story writing training aimed at junior high school students who are teenage age groups. It is hoped that the activities organized for students of SMP N 1 Muaro Jambi can provide motivation and help them develop writing literacy.